Ancient Texts, Papyri, and Manuscripts : Studies in Honor of James R. Royse - Farnes, Alan Taylor,; Mackie, Scott D.,; Runia, David, (New Testament Tools, Studies and Documents ;, 2021)
This volume honors Prof. James R. Royse for his scholarly achievement in the fields of New Testament textual criticism and Philonic studies. It contains seventeen articles, prefaced by an introductory biographical article and a list of his publications.